1999
DOI: 10.1016/s1350-4177(98)00041-8
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of pentachlorophenol aqueous solutions using a continuous flow ultrasonic reactor: experimental performance and modelling

Abstract: The degradation of aqueous solutions of pentachlorophenol (PCP) in a three-stage sonochemical reactor operating in the continuous flow mode has been investigated. The experimental reactor may be considered as a series of three high-frequency ultrasonic units. The influence of several parameters such as ultrasonic power, reactor volume and volumetric feed flow rate on the reactor performance is reported. Application of classical basic chemical engineering principles leads to a model that enables us to predict t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 30 publications
0
38
0
1
Order By: Relevance
“…For example, Zhang and Hua [54] also reported that the rate of degradation of PCBs at 20 kHz was accelerated at higher sound intensities. Gondrexon et al [59] reported, for a continuous flow ultrasonic reactor, an increase of the rate conversion of pentachlorophenol with increasing power input, reaching values of rate conversion close to 80%.…”
Section: Influence Of the Ultrasonic Powermentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Zhang and Hua [54] also reported that the rate of degradation of PCBs at 20 kHz was accelerated at higher sound intensities. Gondrexon et al [59] reported, for a continuous flow ultrasonic reactor, an increase of the rate conversion of pentachlorophenol with increasing power input, reaching values of rate conversion close to 80%.…”
Section: Influence Of the Ultrasonic Powermentioning
confidence: 99%
“…In addition, specific studies, such as the evolution of the pH [39] to acidic values, or the correlation of the molecule properties (vapor pressure) with the kinetics of the process and degradation mechanism [13,40,41,42,43] have been reported. Not only aliphatic compounds but also chlorinated aromatic compounds such as chlorotoluenes [ 44 ], chlorobenzenes [ 45 , 46 , 47 , 48 , 49 ] mixtures of chlorobenzene with trichloroethylene [ 50 , 51 , 52 ], p-chlorobenzoic acid [ 53 ], PCBs [ 54 ], chlorophenols [3,35,48,55,56,57,58,59,60,61] and chlorinated pesticides [58,62,63] have also been the subjects of study, providing a wide range of examples from volatile, nonvolatile, hydrophobic and hydrophilic compounds and their respective behaviors. In the following, the general trends of the operational variables reported in literature and those specifically observed for chlorinated compounds are presented.…”
Section: Influence Of the Operational Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical flow systems have been applied in sonocrystallization [3], water treatment processes [4] and in the production of biodiesel [5]. An increase in reactor volume leads to a simultaneous increase in the ultrasonic power needed to maintain the same power density and owing to the power limitation of each single transducer, a large-scale reactor requires several ultrasonic transducers [6].…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of microcystins by ultrasound of frequency 150 kHz at a 40 W output has recently been reported (Zhang et al, 2005). Pentachlorophenol degradation has similarly been carried out at 500 kHz and 80 W (Gondrexon et al, 1999).…”
Section: Introductionmentioning
confidence: 99%